2017
DOI: 10.1017/s0033291717003324
|View full text |Cite
|
Sign up to set email alerts
|

Secular trends in the prevalence of major and subthreshold depression among 55–64-year olds over 20 years

Abstract: Among late middle-aged adults, there is a substantial net increase of MDD, which is associated with deteriorating physical health. If morbidity and disability continue to increase, a further expansion of MDD rates may be expected. Improving socioeconomic and psychosocial conditions may benefit public health, as these factors were protective against a higher prevalence of both MDD and SUBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 62 publications
(88 reference statements)
3
34
1
Order By: Relevance
“…Several recent studies extending into the 2000s and 2010s report declining frequency of minor or any depression among older persons . A Dutch study on 55‐ to 65‐year‐olds reported a decrease in past‐year subthreshold depression (comparable to minor depression in our study) between 2002 and 2012 for both sexes combined, but an increase in major depression from 1992 and 2002 . Studies on major depression among older persons conducted during the same period report stable prevalence .…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Several recent studies extending into the 2000s and 2010s report declining frequency of minor or any depression among older persons . A Dutch study on 55‐ to 65‐year‐olds reported a decrease in past‐year subthreshold depression (comparable to minor depression in our study) between 2002 and 2012 for both sexes combined, but an increase in major depression from 1992 and 2002 . Studies on major depression among older persons conducted during the same period report stable prevalence .…”
Section: Discussionsupporting
confidence: 61%
“…However, age‐ and sex‐specific projections are uncertain as the prevalence of depression may change over time . An increase in depression is suggested for younger and middle‐aged populations. Among older adults, the prevalence of major depression has been found to be stable , while milder forms of depression have been reported to increase , decrease , or fluctuate over time.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that face‐to‐face interviews conducted in the WMHJ yielded a relatively low prevalence of CMD while self‐report questionnaires conducted in the CSLC yielded relatively high proportions of distress might suggest the possibility of underreporting. However, it is also known that the prevalence of diagnosable mental disorders is not always consistent with the prevalence of subthreshold mental disorders . It is possible that countries with a lower prevalence of diagnosable mental disorders, like Japan, may have a higher prevalence of subthreshold mental disorders.…”
Section: Cross‐national Comparison Of Cmd Prevalencementioning
confidence: 99%
“…However, it is also known that the prevalence of diagnosable mental disorders is not always consistent with the prevalence of subthreshold mental disorders. 43 It is possible that countries with a lower prevalence of diagnosable mental disorders, like Japan, may have a higher prevalence of subthreshold mental disorders.…”
Section: Cross-national Comparison Of Cmd Prevalencementioning
confidence: 99%
“…The existing therapeutic relationship with the physician is an important part of the management of irritable bowel syndrome and can be used to reassure the patient that they can follow the diet and to enhance compliance with diet therapy. 37,38 Patients frequently ask questions regarding the use of alcohol. Alcohol can cause gastrointestinal symptoms by itself.…”
Section: Instructing Patients On the Fodmap Dietmentioning
confidence: 99%